Climate change and the single cell - Derek T. A. Lamport (Academia Biology)
In The Power of Movement in Plants, Charles Darwin details many examples of oscillatory growth, recently exemplified at the single-cell level by pollen tube tip oscillations and associated ion fluxes, particularly of Ca2+and H+. This implies an underlying growth oscillator, supported by the recent discovery that classical arabinogalactan proteins (AGPs) bind Ca2+ at the cell surface. The juxtaposition of AGPs with three additional components embedded in the plasma membrane provides evidence of a Ca2+ cycle that generates cytosolic Ca2+. This cycle involves Ca2+ channels, auxin efflux “PIN” proteins, and an auxin-activated proton pump that dissociates AGP-Ca2+ on demand. While the apparent simplicity of this system satisfies Occam’s razor, its proposed role as a global growth oscillator demands in-depth examination. The wide ramifications extend from pollen tubes to stomatal guard cells. Stomata act as crucial regulatory components of a water hypercycle that contributes to the homeostasis of a warming planet by regulating evaporative cooling and reflective cloud cover generated by vast tropical rainforests of the South and the equally vast arboreal forests of the North. Finally, forests and the high albedo of snow-capped mountains and polar ice caps are essential to the Gaia hypothesis of James Lovelock and Lynn Margulis, which remains a brilliant metaphor despite earlier criticism.